Feasibility study and 3E analysis of blowdown heat recovery in a combined cycle power plant for utilization in Organic Rankine Cycle and greenhouse heating. (1st December 2022) - Saedi, Ali; Jahangiri, Ali; Ameri, Mohammad; Asadi, Farzad
Abstract: Greenhouse heating plays a key role in the growth and yield of greenhouse crops in cold regions. Moreover, heat loss and energy wastage are abundant in the industry. Therefore, these two subjects are combined in this study to analyze the feasibility of using the steam vent and waste drain flow of a blowdown tank in a combined cycle power plant (CCPP) to provide the required additional heating in a greenhouse by installing a radiant floor heating (RFH) system. For this purpose, a tunnel greenhouse with an east-west orientation is modeled in steady states. In addition, a CCPP integrated with the Organic Rankine Cycle (ORC) is modeled on the energy, exergy, and economic (3E) analysis to comprehensively evaluate the system. The effect of greenhouse heating was analyzed in three months of the year with highest heating demand. According to the results of analyzing four scenarios, the RFH system managed to increase the greenhouse temperature up to 7.5 °C. The results indicated an increase in energy efficiency and exergy efficiency of the system by 0.04% and 0.05%, respectively. Based on the economic analysis, the payback period in the proposed scenario was determined 4.81 years. Highlights: Feasibility of using the waste stream of a blowdown tank in a greenhouse is studied. A case study CCPP integrated with the Organic Rankine Cycle (ORC) is modeled. A steady state model is employed to predict the greenhouse energy consumption. The radiant floor heating system is used to heat a greenhouse. 3E analysis is employed to evaluate the performance of the system.